Harmonisasi terhadap Peraturan Tindak Pidana Zina dalam Hukum Islam dan Hukum Pidana - M.Nuril Azra_ (Jurnal Hukum Lex Generalis, 2026)
Adultery is a moral and legal issue addressed differently under Islamic criminal law and Indonesian law. With the enactment of Law No. 1 of 2023 as the national criminal law, questions arise regarding the extent to which the provisions on adultery align with both national criminal law principles and Islamic legal principles. Differences in concepts, elements and criminal liability between the two legal systems make this a significant subject of study. Consequently, this research employs a normative-juridical method with a comparative approach to examine points of convergence, divergence and opportunities for harmonizing the regulation of adultery.